Environmental carcinogenic polycyclic aromatic hydrocarbons in soil from Himalayas, India: Implications for spatial distribution, sources apportionment and risk assessment. (February 2016) - Devi, Ningombam Linthoingambi; Yadav, Ishwar Chandra; Shihua, Qi; Dan, Yang; Zhang, Gan; Raha, Priyankar
Abstract: The Indian Himalayan Region (IHR) is one of the important mountain ecosystems among the global mountain system which support wide variety of flora, fauna, human communities and cultural diversities. Surface soil samples (n = 69) collected from IHR were analysed for 16 priority polycyclic aromatic hydrocarbons (PAH) listed by USEPA. The ∑16 PAH concentration in surface soil ranged from 15.3 to 4762 ngg −1 (mean 458 ngg −1 ). The sum total of low molecular weight PAH (∑LMW-PAHs) (mean 74.0 ngg −1 ) were relatively lower than the high molecular weight PAH (∑HMW-PAHs) (mean 384 ngg −1 ). The concentration of eight carcinogenic PAHs (BaA, CHR, BbF, BkF, BaP, DahA, IcdP, BghiP) were detected high in mountain soil from IHR and ranged from 0.73 to 2729 ngg −1 (mean 272 ngg −1 ). Based on spatial distribution map, high concentration of HMW- and LMW-PAHs were detected at GS1 site in Guwahati (615 and 4071 ngg −1 ), and lowest concentration of HMW-PAHs were found at IS6 in Itanagar (5.80 ngg −1 ) and LMW-PAHs at DS2 (17.3 ngg −1 ) in Dibrugarh. Total organic carbon (TOC) in mountain soil was poorly connected with ∑PAHs ( r 2 = 0.072) and Car-PAHs ( r 2 = 0.048), suggesting the little role of TOC in adsorption of PAHs. Isomeric ratio of PAHs showed the source of PAH contamination in IHR is mixed of petrogenic and pyrogenic origin and was affirmed by PAHs composition profile. These source apportionment results were further confirmed by principal component analysis (PCA). Eco-toxicological analysis showed the calculated TEQ for most carcinogenic PAH were 2–4 times more than the Dutch allowed limit, while TEQ of BaP was 25 times high, suggesting increasing trend of carcinogenicity of surface soil. Graphical abstract: Highlights: Total PAHs concentration were detected high in IHR. High molecular weight PAHs were relatively higher than low molecular weight PAH. TOC play little role in adsorption of PAH in mountain soil of IHR. TEQ analysis showed increasing level of PAH contamination in soil.